What is the “modified” CTAB protocol? Characterizing modifications to the CTAB DNA extraction protocol - Schenk, John J.; Becklund, L. Ellie; Carey, S. James; Fabre, Paige P. (Applications in plant sciences, 2023)
Cetyltrimethylammonium bromide (CTAB)–based methods are widely used to isolate DNA from plant tissues, but the unique chemical composition of secondary metabolites among plant species has necessitated optimization. Research articles often cite a “modified” CTAB protocol without explicitly stating how the protocol had been altered, creating non‐reproducible studies. Furthermore, the various modifications that have been applied to the CTAB protocol have not been rigorously reviewed and doing so could reveal optimization strategies across study systems. We surveyed the literature for modified CTAB protocols used for the isolation of plant DNA. We found that every stage of the CTAB protocol has been modified, and we summarized those modifications to provide recommendations for extraction optimization. Future genomic studies will rely on optimized CTAB protocols. Our review of the modifications that have been used, as well as the protocols we provide here, could better standardize DNA extractions, allowing for repeatable and transparent studies.